Nightmare distress, nightmare frequency, and beliefs about nightmares - Schredl, Michael; Holyba, Louisa; Köllmer, Tina; Körfer, Jessica; Proß, Annika (International journal of dream research, 2019)
The diagnosis of a nightmare disorder is based on clinically significant distress caused by the nightmares and, therefore, empirical research should focus on studying factors that affect nightmare distress in addition to nightmare frequency. Overall, 2056 persons (1212 woman, 844 men) completed the online survey. A reliable 6-item scale measuring beliefs about nightmares was developed. The beliefs about nightmares scale contributed to nightmare distress independently from nightmare frequency. From a clinical viewpoint, it would be desirable to carry out intervention studies looking at the effect of psychoeducation about nightmares on nightmare frequency and nightmare distress.
Gesehen am 07.10.2019